Reaction kinetics and pathways of crotonic acid conversion in sub- and supercritical water for renewable fuel production. Issue 2 (1st December 2021) - Gubatanga, Diane Valenzuela; Sawai, Osamu; Nunoura, Teppei
Abstract : The degradation of an unsaturated lipid compound in water proceeds via two temperature-driven pathways – ionic and free radical reaction pathways. Abstract : Conversion of waste lipid biomass into renewable fuels using sub- and supercritical water provides an alternative green approach in contrast with the current treatment methods. However, the reaction network of unsaturated lipids in sub- and supercritical water has not been clarified. Unsaturated lipids are found abundantly in waste lipid biomass, making the establishment of their reaction network essential. In this study, the reaction of crotonic acid (CA) as a model unsaturated lipid in sub- and supercritical water was clarified through an in-depth study of its reaction pathways and kinetics. The experiments were conducted at temperatures from 300 to 415 °C, a pressure of 25 MPa, and residence times from 30 to 150 s in a continuous flow process. The main products in the initial stage of the reaction were butyric acid (BA) and propene. Based on the temperature dependence experiments, the CA conversion increased along with temperature and residence time. Based on the product distribution, two main decomposition pathways were identified in the initial stage of the CA reaction. The first is CA direct decarboxylation and the second is CA hydrogenation followed by BA decarbonylation. Examination of the kinetic rates revealed that the reaction mainly proceeds via CA direct decarboxylation, contrary to the results reported in previous studies. The findings demonstrated that the role of water can change according to the conditions and reactions employed. This was proven by the evident variation of kinetic rate constants under sub- and supercritical conditions and is reflected in the Arrhenius plot.